Examining sensory gating and processing speed in adults with autism using EEG - Jacoby, Erica C., author; Davies, Patricia, advisor; Stephens, Jaclyn, committee member; LaGasse, Blythe, committee member (Colorado State University. Libraries, 2018)
Objectives. Most individuals with Autism Spectrum Disorder (ASD) experience sensory deficits in their auditory processing (Tomchek & Dunn, 2007). These deficits can further impact their ability to participate in their physical and social environments. One way to increase understanding of these deficits is through use of electroencephalography (EEG), which measures brain activity in real-time and is able to distinguish brain processes such as sensory processing and the deficits that might be occurring during this process (Davies & Gavin, 2007). This study's purpose is to understand how processing speed and ability to filter out irrelevant stimuli impacts adults with ASD compared to their neurotypical (NT) peers through measurements of latency of prominent brain activity following presentation of an auditory stimulus and sensory gating. This study also analyzed how active and passive attention states impact sensory gating and latency. Methods. 24 adults with autism (M = 23.3 years, SD = 3.8) and 24 neurotypical adults (M = 23.7 years, SD = 3.5) participated in this study. They completed a sensory gating paradigm in both an active and a passive listening condition. In the active condition they were asked to press a button when they heard a single click, and in the passive condition they simply stared at a static image on a screen while the auditory stimuli were presented to them. Results. The results showed that there are no significantly different sensory gating responses between the ASD and NT groups. Individuals with ASD had delayed processing speed as measured through latency as early as 100 milliseconds following an auditory stimulus. Both groups experienced slower processing in the passive condition starting at approximately 200 milliseconds post-stimulus onset. As expected, more gating was observed for both groups in the passive condition at early components, where-as the active condition - which required attention to the stimulus that is usually suppressed in this task - resulted in less gating. In the latest component analyzed, approximately 200 milliseconds post-stimulus, both groups showed more gating in the active attention state, which was the opposite of the expected results, and the possible reason for this unexpected result needs further exploration. Conclusions. These findings suggest that individuals with autism do not have deficits in the ability to filter out irrelevant stimuli, however, they are likely more impacted by delayed processing speeds. Implications for practice include allowing more time to process auditory information for individuals with autism, and using compensatory strategies to influence neural processing speeds and amount of gating in response to auditory stimuli through the use of activity demands to create either passive or active attention states.
Keywords: autism; processing speed; sensory processing disorder; ASD; sensory gating; EEG